Skills in Completing KPSP: An Android-Based Pre-Developmental Screening Questionnaire of Diploma Midwifery Students - Neli Sunarni; Aulia Ridla Fauzi (Inspirasi Foundation, 2022)
Objective: To find out the description of student skills in filling in the Android-Based Pre-Developmental Screening Questionnaire. Method: This type of research is descriptive quantitative, the population in this study is Level II Semester IV students of Diploma Midwifery STIKes Muhammadiyah Ciamis as many as 23 people, the sample is taken using a total sampling technique, namely, the entire population is sampled, the analysis used in this research is univariate analysis, an instrument using the Android-Based Pre-Developmental Screening Questionnaire filling assessment checklist sheet. Result: The study's results showed that out of 23 students scored a quality of 4.0 with an A symbol, of 48%. Conclusion: In this study, it can be concluded that student skills in completing the Android-based KPSP are declared to obtain a passing score.